Framework for co-development of an open hydrological data system to enhance climate resilience in climate vulnerable countries: experience from a digital groundwater monitoring pilot in Nepal - Urfels, Anton; Shakya, S. M.; Maharjan, S.; Lohanee, B. D.; Pandey, V.; Khadka, Manohara; Adhikari, S.; Neupane, A.; Karki, S.; Acharya, S.; Foster, T.; Krupnik, Timothy J. (Copernicus GmbH, 2021)
Groundwater constitutes the major source of global freshwater supply - making groundwater data critical for supporting adaptation to climate change. This is especially relevant for climate vulnerable countries like Nepal, where the data needed to characterise water security risks is often either not collected, not made available, or does not meet the needs and interests of decision makers. This constitutes a gap between the availability and demand of hydrological data. Countries have limited capacity for streamlined hydrological research and data collection, which does not correspond to the numerous needs and stakeholder’s interest to handle water stress in agriculture, maintain adequate water supply for biodiversity, and ensure that drinking water is of sufficient quality. A systematic framework for reconciling these capacities and stakeholder interests is therefore necessary. Through the development of an open data collection system, the framework can (i) provide an inclusive space for multi-stakeholder dialogue and (ii) substantiate debates on water resources management and policy – both of which are currently disconnected from each other and from the hydrological realities. Without following an integrated framework, initial pilots to build open hydrological data systems are less likely to be effective as they do not deliver on their potential synergy and cross-sectoral benefits that go in hand increased awareness of scientists about the needs and interest in hydrological data for different user groups.